Communication Styles Used by Male and Female Teachers’ in EFL Classroom Interaction - Rahmaeni, Rahmaeni (Maspul Journal of English Studies, 2023)
Teachers’ communication style plays an important role in teaching and learning process because the students’ success in learning will be significantly influenced by styles that the teacher used to communicate with the students. Therefore, it is important to investigate the styles of communication used by teachers in the classroom. This research focused on exploring the communication styles used by male and female teachers in EFL classroom, the similarities and the differences between male and female teachers’ communication styles, and the aspects influencing their communication styles. This research was based on a study conducted at State University of Makassar, particularly in English Education Department, in September 2018. This study involved two male teachers and two female teachers of English Education Department. To collect data, the researcher recorded teaching process carried out by the four teachers in the classroom. Each teacher was recorded in two meetings, so eight recordings from the four teachers were obtained, transcribed, and analyzed by using discourse analysis approach. The communication styles used by teachers were analyzed based on the theory of communication style by Mikoluk (2013) and Lanz (2015). The findings showed that there were four communication styles used by male and female teachers in EFL classroom. They were assertive, aggressive, passive, and passive-aggressive styles. Male teachers were more dominant than the female teachers in the use of assertive, aggressive, and passive style, whereas female teachers were more dominant than the male teachers for passive-aggressive style. In addition, there were 3 aspects that influenced the teachers’ communication style. They were classroom atmosphere, teaching time, and subject taught. Findings of this study were advantageous to expand insights about communication style used by teachers in EFL classroom, including how it affected the teaching process and what aspects influence the communication style. Those insights then became consideration for EFL teachers to improve their teaching performance.